Excess non‐psychiatric hospitalizations among employees with mental disorders: a 10‐year prospective study of the GAZEL cohort. (7th October 2014) - Azevedo Da Silva, M.; Lemogne, C.; Melchior, M.; Zins, M.; Van Der Waerden, J.; Consoli, S. M.; Goldberg, M.; Elbaz, A.; Singh‐Manoux, A.; Nabi, H.
<x xml:space="preserve">Abstract</x> Objective To examine whether non‐psychiatric hospitalizations rates were higher in those with mental disorders. Method In a cohort of 15 811 employees, aged 35–50 years in 1989, mental disorder status was defined from 1989 to 2000. Hospitalizations for all‐causes, myocardial infarction (MI), stroke, and cancer, were recorded yearly from 2001 to 2011. Negative binomial regression models were used to estimate hospitalization rates over the follow‐up. Results After controlling for baseline sociodemographic factors, health‐related behaviors, self‐rated health, and self‐reported medical conditions, participants with a mental disorder had significantly higher rates of all‐cause hospitalization [incidence rate ratio, IRR = 1.20 (95%, 1.14–1.26)], as well as hospitalization due to MI [IRR = 1.44 (95%, 1.12–1.85)]. For stroke, the IRR did not reach statistical significance [IRR = 1.37 (95%, 0.95–1.99)] and there was no association with cancer [IRR = 1.01 (95%, 0.86–1.19)]. A similar trend was observed when mental disorders groups were considered (no mental disorder, depressive disorder, mental disorders due to psychoactive substance use, other mental disorders, mixed mental disorders, and severe mental disorder). Conclusion In this prospective cohort of employees with stable employment as well as universal access to healthcare, we found participants with mental disorders to have higher rates of non‐psychiatric hospitalizations.